2021
DOI: 10.1186/s12979-021-00254-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T and B cell subsets in end stage renal disease patients before and after kidney transplantation

Abstract: Background The incidence of kidney transplantation performed in elderly patients has increased steadily recently. Higher risk of infection and mortality, but lower rate of rejection, are reported in older kidney transplant patients. This study aims to analyze the effect of transplantation on aging of T and B cells in kidney transplant patients, with the emphasis on age and Cytomegalovirus (CMV) latency. Results We included 36 patients before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
4
7
0
Order By: Relevance
“…End-stage renal disease (ESRD) is one of the major causes of concern for human health. At present, the most effective treatment is renal transplantation, however, rejection remains a major threat and is a primary independent risk factor affecting the long-term survival of the transplanted kidney ( 1 , 2 ). In addition, cABMR is a serious threat to the long-term survival of the transplanted kidney which needs attention ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…End-stage renal disease (ESRD) is one of the major causes of concern for human health. At present, the most effective treatment is renal transplantation, however, rejection remains a major threat and is a primary independent risk factor affecting the long-term survival of the transplanted kidney ( 1 , 2 ). In addition, cABMR is a serious threat to the long-term survival of the transplanted kidney which needs attention ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the decrease in the ratio of B cells to CD28-CD8+ T cells and the increase in the ratio of CD28-CD8+ T cells to Tregs can be explained at least in part by the increase in CD28-CD8+ T cells. On the other hand, the association between B cell frequency and CMV status is less well-documented ( 29 , 31 ). The effect of CMV on lymphocyte phenotypes in transplant recipients is an interesting issue necessitating further research but is beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…We found that compared to the CMV group 0, the other groups had a significant decrease in B cell percentage (Tables 2, 3), a significant decrease in the ratio of B cells to CD28- CD8+ T cells (Tables 4, 5), and a significant increase in the ratio of CD28-CD8+ T cells to Tregs (Tables 6, 7). Several recent studies have shown that kidney transplant patients with positive CMV serology have higher frequency of CD28-CD8+ T cells compared to those with negative CMV serology (28)(29)(30). Therefore, the decrease in the ratio of B cells to CD28-CD8+ T cells and the increase in the ratio of CD28-CD8+ T cells to Tregs can be explained at least in part by the increase in CD28-CD8+ T cells.…”
Section: Rejection Of All Types Is Associated With An Increase In The...mentioning
confidence: 99%
“…This leads to an altered immunological landscape in SOT recipients, resulting in differing host responses to severe infections, including from SARS-CoV-2. SOT recipients at baseline have decreased frequencies of circulating naïve T and NK cells, and an increased frequency of terminally differentiated and senescent T cells compared with the general population [11][12][13] . Few studies, however, have pro led the immune landscape of SOT recipients in the context of severe infection, and none have yet used a multi-omic approach to assess their responses at the cellular, protein, transcriptional, and microbial levels.…”
Section: Introductionmentioning
confidence: 97%